Prevalence of fluoroquinolone resistance-associated mutations in Mycoplasma genitalium among clients of two sexual health centres in the Netherlands: a cross-sectional study - Henry J C de Vries; Sylvia M Bruisten; David Hetem; Clarissa Vergunst; Helene C A Zondag; Alje P van Dam; Maarten F Schim van der Loeff; Joyce F Braam (BMJ Open)
Objective This study aimed to determine the prevalence of fluoroquinolone resistance-associated mutations (QRAMs) in Mycoplasma genitalium (MG) among clients of two sexual health centres (SHCs) in the Netherlands.Design A cross-sectional study.Setting and participants Between 2018 and 2019, 669 clients with MG were included from two previous studies: 375 male clients with urethritis from the SHC in Amsterdam; and 294 clients (male and female) from the SHC in Amsterdam and The Hague. Urogenital and anal samples (705 in total) that tested positive for MG by nucleic acid amplification tests were selected.Outcome measures The presence of QRAM was detected by an MG-QRAM PCR targeting four mutations in the parC gene and investigated by sequence analysis of relevant regions of the gyrA and parC genes. Possible risk factors for the presence of QRAM were investigated.Results We found QRAM in 58 of 669 (9%) clients with an MG infection: 36 of 375 (10%) in the study population of men with urethritis and 22 of 294 (7%) in the study population of other clients (including both men and women; p=0.334). Most prevalent mutations in the parC gene were S83I and D87N, occurring in 31 of 60 (52%) and 20 of 60 (33%) samples, respectively. Factors associated with the presence of QRAM were: men who have sex with men (adjusted OR (aOR) 3.4, 95% CI 1.7 to 6.9) and Asian origin (aOR 2.5, 95% CI 1.2 to 5.6). Multidrug resistance (QRAM plus macrolide resistance-associated mutations) was found in 46 of 669 (7%) clients.Conclusions Nine per cent of MG-positive clients from two Dutch SHCs had QRAM. New treatment strategies and antibiotics are needed to treat symptomatic patients with multidrug-resistant MG.